Aislamiento de Acanthamoeba en pacientes del Servicio de Oftalmología del Hospital Nacional Cayetano Heredia - Suárez, Roxana (2002)
Objective: To determine the presence of Acanthamoeba genus in symptomatic persons. Setting: Cayetano Heredia National Hospital Ophthalmology Service. Material and methods: One hundred individuals without evidence of corneal lesion had corneal samples examined during April and May 1999. Samples were sowed in neapolitan agar and non-nutritive agar, incubated and checked after 7 days. Results: Acanthamoeba cysts were found in 16 out of the 100 samples; 44 subjects were male; diagnosis was not different in both sexes; 63% of individuals were below 20 year-old; infection was predominant in younger people; 89% referred visits to areas where the parasite had been reported (Piura, Ica); 58 subjects referred swimming in pools or rivers. Out of 76 subjects who reported daily use water source, 63% obtained it from water-tank cars and 25% from wells; infection was more frequent in the latter ones (31,6% vs. 12,5%). Acanthamoeba coincided with amethropy (44%), conjunctivitis (16,4%) and blepharitis (12,3%). Conclusion: The parasite Acanthamoeba is present in young people without corneal lesion in whom risk to develop keratitis has to be considered.